Effect of RNAi therapeutics patisiran and vutrisiran on orthostatic hypotension due to dysautonomia in patients with hereditary transthyretin-mediated amyloidosis with polyneuropathy. (3rd October 2022) - Slama, M; Obici, L; Okumura, T; Arum, S; Hale, C; Jay, P Y; Capocelli, K; Gonzalez-Duarte, A
Abstract: Background: Hereditary transthyretin-mediated (hATTR) amyloidosis, also known as ATTRv amyloidosis, is a rapidly progressive, multisystem disease. Orthostatic hypotension, due to autonomic neuropathy, is a common yet hard-to-treat disease manifestation in patients with hATTR amyloidosis. Fatigue, muscle weakness, and deterioration in cardiac function further exacerbate orthostatic symptoms. Efficacy of RNAi therapeutics patisiran and vutrisiran was assessed in patients with hATTR amyloidosis with polyneuropathy across the APOLLO (NCT01960348), Global Open-Label Extension (OLE) (NCT02510261), and HELIOS-A (NCT03759379) studies, respectively. Purpose: Evaluate the quantitative effect of patisiran and vutrisiran on orthostatic hypotension in patients with hATTR amyloidosis with polyneuropathy. Methods: In APOLLO, patients were randomised 2:1 to patisiran 0.3 mg/kg or placebo, IV q3w. Patients who completed APOLLO (APOLLO-placebo, APOLLO-patisiran) were eligible to enrol into the ongoing Global OLE (patisiran 0.3 mg/kg IV q3w). In HELIOS-A, patients were randomised 3:1 to vutrisiran (25 mg SC q3m) or patisiran (0.3 mg/kg IV q3w; reference group). Primary endpoint for APOLLO and HELIOS-A was change from baseline in the modified Neuropathy Impairment Score+7 (mNIS+7) vs APOLLO placebo at M18 (APOLLO) and M9 (HELIOS-A). Orthostatic hypotension was evaluated using the postural blood pressure (PBP) component of mNIS+7, calculated as the mean of 2 supine readings of systolic BP [SBP, mmHg] taken 15 min apart minus the lowest SBP upon standing at 1, 3, and 5 min. A smaller reduction in observed SBP between supine and upright readings indicated an improved PBP. Results: APOLLO enrolled 225 patients (placebo, n=77; patisiran, n=148), Global OLE 211 and HELIOS-A 164 (vutrisiran, n=122; patisiran, n=42). At baseline, the severity of orthostatic hypotension was similar between within-study treatment arms in APOLLO and HELIOS-A. In APOLLO, patisiran-treated patients showed PBP improvement or stabilization from baseline to M18 (mean [SD] change in SBP: baseline, −17.6 [19.4]; M18, −13.5 [16.8]) and was maintained at Global OLE 36m (−13.4 [15.6]). In contrast, placebo-treated patients in APOLLO had an increased change in PBP over 18m (baseline, −17.5 [16.5]; M18, −20.4 [16.9]); their PBP improved after patisiran initiation (Global OLE 36m, −16.6 [18.1]). In HELIOS-A, stabilization in PBP was observed in the vutrisiran arm (baseline, −11.2 [14.0], M18, −11.7 [14.6]). In the smaller patisiran arm, while the change in PBP increased, the value remained in the normal range (baseline, −11.6 [17.2]; M18, −14.2 [15.5]). Patisiran and vutrisiran have acceptable safety profiles. Conclusions: PBP analyses quantify the benefits of RNAi therapeutics patisiran and vutrisiran on autonomic function in patients with hATTR amyloidosis with polyneuropathy. The increase in change in PBP to a symptomatic range without treatment indicates the importance of early intervention. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Alnylam Pharmaceuticals